Pedagogical Prophet? David Hargreaves' 1996 Vision for a Research-Based Profession: A 2024 Reality Check - Andrew Jones (PRISM)
David Hargreaves' 1996 vision for a research-based teaching profession aimed to integrate robust, evidence-based approaches into educational practice and policy. This critical evaluation examines the extent to which his vision has been realised. In his inaugural lecture for the Teacher Training Agency (TTA), Hargreaves proposed a profession where research directly informs teaching practices, promoting continuous improvement in educational outcomes. This evaluation compares his proposals with the current educational landscape, highlighting both progress and ongoing challenges. While acknowledging Hargreaves' significant influence, the analysis also considers criticisms regarding the types of research that have become prevalent in educational discourse, especially within government policy. The article underscores the need for ongoing development to fully achieve a research-based profession and evaluates the impact of Hargreaves' ideas on contemporary educational policy and practice.